2021
DOI: 10.3390/e23040419
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Performance Optimization of an Irreversible Two-Stage Combined Thermal Brownian Heat Engine

Abstract: Based on finite time thermodynamics, an irreversible combined thermal Brownian heat engine model is established in this paper. The model consists of two thermal Brownian heat engines which are operating in tandem with thermal contact with three heat reservoirs. The rates of heat transfer are finite between the heat engine and the reservoir. Considering the heat leakage and the losses caused by kinetic energy change of particles, the formulas of steady current, power output and efficiency are derived. The power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 124 publications
0
9
0
Order By: Relevance
“…A large number of works have been performed for reciprocating (finite time) models [16][17][18][19][20][21][22][23][24][25] by applying FTT. While finite size is the major feature for steady-flow devices, such as closed gas rubine (Brayton cycle) power plants and steam (Rankine cycle) and organic Rankine cycle power plants, many scholars have performed FTT studies for various steady-flow cycles with the power output (POW), thermal efficiency (TEF), exergy efficiency, profit rate, and ecological function as the optimization goals, under the conditions of different losses and heat transfer laws .…”
Section: Introductionmentioning
confidence: 99%
“…A large number of works have been performed for reciprocating (finite time) models [16][17][18][19][20][21][22][23][24][25] by applying FTT. While finite size is the major feature for steady-flow devices, such as closed gas rubine (Brayton cycle) power plants and steam (Rankine cycle) and organic Rankine cycle power plants, many scholars have performed FTT studies for various steady-flow cycles with the power output (POW), thermal efficiency (TEF), exergy efficiency, profit rate, and ecological function as the optimization goals, under the conditions of different losses and heat transfer laws .…”
Section: Introductionmentioning
confidence: 99%
“…As a further extension of traditional irreversible process thermodynamics, finite-time thermodynamics (FTT) [1][2][3][4][5][6][7][8][9][10][11] has been applied to analyze and optimize performances of actual thermodynamic cycles, and great progress has been made. FTT has been applied in micro-and nano-cycles [12][13][14][15], thermoelectric devices [16,17], thermionic devices [18,19], gas turbine cycles [20][21][22], internal combustion cycles [23,24], cogeneration plants [25,26], thermoradiative cell [27], chemical devices [28,29], and economics [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the combined HE had three operating modes with different temperatures of WM, and the improving extents of power and efficiency linearly increased with the number of stages. For thermal Brownian engines, Qi et al [ 94 , 95 ] studied the combined thermal Brownian HE [ 94 ] and refrigerator [ 95 ] by using FTT theory. To date, the combined HE using ideal quantum gas as WM has not been studied in the open literature.…”
Section: Introductionmentioning
confidence: 99%